Burkina Faso Indigenous Innovation in Farmer-to-Farmer Extension - World Bank (Washington, DC, 2012)
Increasing attention is being given to indigenous innovation in agriculture - the process by which farmers develop new and better ways of doing things, primarily using local resources and on their own initiative, without pressure or direct support from formal research or development agents. In this process, farmers have developed not only better farming techniques but also better ways of organizing themselves. In the Yatenga Region of Burkina Faso, local improvements on a traditional farming technique have become very widespread, largely on account of the innovativeness of farmers in developing their own forms of farmer-to-farmer extension. They have found highly effective ways of spreading their ideas and encouraging other farmers to try them out.